Peningkatan Capacity Building Aparatur Nagari Suayan dalam Pemanfaatan Kios SKM dan Menganalisis Data Survey Kepuasan Masyarakat - Dasman Lanin; Boni Saputra; Lince Magriasti; Afifah Asriati; Dwi Finna Syolendra; Muhammad Nasrullah (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service activity is an advanced stage for the second year, funded by the Institute for Research and Community Service (LPPM) Universitas Negeri Padang. This activity aims to assist in increasing the knowledge and skills of Nagari Suayan officials in conducting technology-based community satisfaction surveys (SKM) in the form of utilizing SKM kiosk machines and activities to analyze SKM results data. The SKM Kiosk is an SKM survey recording machine that utilizes digital technology. The method in this activity uses training and mentoring, "participatory extension". The results achieved in this activity included the following: Apparatus became skilled and accustomed to using/utilizing SKM Kiosk machines, making it easier for them to record SKM surveys and apparatus were also able to analyze and process SKM results data and were able to interpret data analysis results and be able to provide solutions or breakthroughs (innovations) in realizing services that satisfy the community towards excellent service in the Nagari.